1927 Haw. Sess. Laws 209-17, §§ 1, 4 - (:unkn) unknown (My University, 1927)
AN ACT Regulating the Sale, Transfer and Possession of Certain Firearms and Ammunitions, and Amending Sections 2136, 2137, 2138, 2139, 2140, 2141, 2142, 2143, 2146 and 2147 of the Revised Laws of Hawaii 1925 (the "Small Arms Act"), § 1, § 4: Defined pistol or revolver having a barrel less than twelve inches in length. Defined crimes of violence as murder, manslaughter, rape, mayhem,, assault to do great bodily harm, robbery, larceny, burglary, and house-breaking. Persons convicted of these crimes are prohibited from possessing a pistol or revolver.
Keywords: DEFINITIONS; POSSESSION - DANGEROUS PERSONS